Study of Fiqhul Hadith on the Law of Alms to Thieves, Adulterers and the Rich - Lendrawati, Lendrawati; Supian, Aan; Marhayati, Nelly; Jalili, Ismail (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Giving to a person either in the form of compulsory alms (zakat) or ordinary alms already has a designated recipient or musthiq. This research elaborates on the law of almsgiving to thieves, adulterers and the rich. The research used is a review of literature through the takhrij al-hadith method both in terms of the quality of sanad and matan. The result of his research is that almsgiving to thieves, adulterers and the rich can be viewed from the side of maslahat, the highlighted object is the recipient not the one who gives alms. In this case almsgiving becomes a will away from forbidden deeds according to the rules of fiqh li al-wasail hukmu al-maqasid (the law of intermediary depends on its purpose). Almsgiving can be a testament and the media prevents the sipencuri from stealing, prevents the adulterer from committing adultery and gives motivation to the sikaya to immediately issue his zakat or alms.